Doxycycline Combined with NB-UVB Phototherapy for Acquired Reactive Perforating Collagenosis - Gao L; Gu L; Chen Z; Cao S (Dove Medical Press, 2020)
Limu Gao, Lixiong Gu, Zhen Chen, Shuanglin Cao Department of Dermatology, Affiliated Hospital of Nantong University, Nantong, Jiangsu Province, People’s Republic of ChinaCorrespondence: Shuanglin CaoDepartment of Dermatology, Affiliated Hospital of Nantong University, 20th Xisi Road, Nantong, People’s Republic of ChinaEmail slcao@medmail.com.cnBackground: Acquired reactive perforating collagenosis is a rare skin disease characterized by the discharge of collagen fibers through the epidermis. There is no standard treatment for this disease currently. Here, we report a case of ARPC that has been successfully treated and cured.Case Description: A 32-year-old man developed severe itching papules on his torso and limbs for 3 months. Skin lesions were keratotic papules scattered on the limbs and trunk, with a diameter of 3 to 12 mm. Some lesions had umbilical recesses and the shape of a crater with positive isomorphic reactions. The patient scratched his severe itching lesions which merged into large ones. This patient had histories of hypertension and dilated cardiomyopathy with mild congestive heart failure. The clinical presentation and histopathology of skin lesions met Faver’s diagnostic criteria for ARPC.Treatment: Oral Doxycycline 100mg/d, NB-UVB phototherapy 3 times a week with initial dose 400mJ/cm2, gradually increased to 1200mJ/cm2(total cumulative dose 16700J/cm2).Outcomes: After a week of treatment, the patient’s itching symptoms were significantly reduced and stopped presenting any new skin lesions. Most of the lesions healed in 6 weeks of treatment.Lessons: Doxycycline combined with NB-UVB may be an effective treatment for ARPC.Keywords: acquired reactive perforating collagenosis, doxycycline, NB-UVB, hypertension